Measurements of air dose rates in and around houses in the Fukushima Prefecture in Japan after the Fukushima accident - Matsuda, Norihiro; Mikami, Satoshi; Sato, Tetsuro; Saito, Kimiaki (Journal of environmental radioactivity, 2017)
Measurements of air dose rates for 192 houses in a less contaminated area (<0.5 μSv h−1) of the Fukushima Prefecture in Japan were conducted in both living rooms and/or bedrooms using optically stimulated luminescence (OSL) dosimeters and around the houses via a man-borne survey at intervals of several meters. The relation of the two air dose rates (inside and outside) for each house, including the background from natural radionuclides, was divided into several categories, determined by construction materials (light and heavy) and floor number, with the dose reduction factors being expressed as the ratio of the dose inside to that outside the house. For wooden and lightweight steel houses (classed as light), the dose rates inside and outside the houses showed a positive correlation and linear regression with a slope-intercept form due to the natural background, although the degree of correlation was not very high. The regression coefficient, i.e., the average dose reduction factor, was 0.38 on the first floor and 0.49 on the second floor. It was found that the contribution of natural radiation cannot be neglected when we consider dose reduction factors in less contaminated areas. The reductions in indoor dose rates are observed because a patch of ground under each house is not contaminated (this is the so-called uncontaminated effect) since the shielding capability of light construction materials is typically low. For reinforced steel-framed concrete houses (classed as heavy), the dose rates inside the houses did not show a correlation with those outside the houses due to the substantial shielding capability of these materials. The average indoor dose rates were slightly higher than the arithmetic mean value of the outdoor dose rates from the natural background because concrete acts as a source of natural radionuclides. The characteristics of the uncontaminated effect were clarified through Monte Carlo simulations. It was found that there is a great variation in air dose rates even within one house, depending on the height of the area and its closeness to the outside boundary. Measurements of outdoor dose rates required consideration of local variations depending on the environment surrounding each house. The representative value was obtained from detailed distributions of air dose rates around the house, as measured by a man-borne survey. Therefore, it is imperative to recognize that dose reduction factors fluctuate in response to various factors such as the size and shape of a house, construction materials acting as a shield and as sources, position (including height) within a room, floor number, total number of floors, and surrounding environment. •Dose reduction factor (RF) was summarized from measurements around 200 houses in a less contaminated area of Fukushima.•Reductions in indoor dose rates were found to occur with the existence of an uncontaminated area.•In this study, this effect was referred to as the “uncontaminated effect”.•For measurement of outdoors, a man-borne survey around the house was an effective way to obtain the detailed distribution.•It is imperative to recognize that RF fluctuates with various factors related to a house and its surrounding environment.